A little taste of freedom : the Black freedom struggle in Claiborne County, Mississippi - Crosby, Emilye (John Hope Franklin series in African American history and culture., 2005)
A community study of the freedom movement in rural, majority-black Claiborne County, Mississippi that explores the impact of the African American freedom struggle on small communities. It analyzes the political and economic issues in the postmovement period, and the impact of the movement and the resilience of white supremacy.